Annotated record of the detailed examination of Mn deposits from DSDP Site 63, Leg 7 (Cores 63-1, 63-10, 63A-1, 63B-1) - Edward L Winterer; William R Riedel; Ralph Moberly; Johanna M Resig; Loren W Kroenke; E L Gealy; G Ross Heath; P Bronnimann; E Martini; Thomas R Worsley (PANGAEA, 1971)
The sedimentary section at Site 62 on Eauripik Ridge can be traced eastward into the East Caroline Basin. It was decided to drill a hole to basement in the eastern part of East Caroline Basin to determine the age of the upper strong reflectors and to test the hypothesis that sediments older than any at Site 62 are present. A nearly complete section was obtained from middle Oligocene to Quaternary, unconformably overlying basalt containing middle Oligocene chalk xenoliths. The sediments consist of chalk and chalk ooze in the Oligocene and Miocene, and of marl ooze and calcareous clay in the Pliocene and Quaternary.
Supplement to: Winterer, EL et al. (1971): Site 63. In: Winterer, E.L.; et al., Initial Reports of the Deep Sea Drilling Project, 7, Initial Reports of the Deep Sea Drilling Project, 7, U.S. Government Printing Office, VII, 323-472, https://doi.org/10.2973/dsdp.proc.7.105.1971